Graded Recession for Primary Inferior Oblique Over Action - Captain Muhahmmad Zaheer, Asad Ali Asim, Sharif Hashmani, Muhammad Ather Jamil (Pakistan Journal of Ophthalmology, 2018)
Purpose: To evaluate the results of graded recession of inferior oblique for primary inferior oblique over action. Material and Methods: Ten patients were selected from OPD of Lakson Medical Trust, Sahiwal having primary inferior oblique over action with V pattern of more than 5 degrees. Bilateral graded inferior oblique recession was carried out using a Fink’s caliper. Final follow-up was at one year. Results: Mean age of the patients was 15.7 years. Mean Pre operative V pattern was 7.5 degrees (15PD). Mean post operative V pattern was 1.6 degrees (3.2 PD). Mean pre-op extortion in primary position was 4.3 degrees. It was decreased to mean post operative value of 1.3 degrees. Cyclo vertical diplopia was also corrected that was present in one patient. Conclusions: Graded inferior oblique recession by Fink’s Method is an effective procedure to correct cyclo vertical deviations due to Primary inferior oblique over action. It also improved cyclovertical diplopia in few cases.